An Overview of Justice in Sir Walter Scott Waverley Novels: The Heart of Mid-Lothian - Enrique García Díaz (Oñati Socio-Legal Series)
Although Sir Walter Scott is a well-known writer most of his readers know that he became an advocate in 1792, when he was admitted to the bar. Since then Scott and other advocates walked the floor at Parliament House (home of the Faculty of Advocates and the Court of Session) waiting to be hired. Scott’s own experiences as a fledgling advocate are echoed in those of Alain Fairford in his novel Redgauntlet (Scott 1824), which provides a vivid picture of Parliament House in the eighteenth century. During his life, Scott combined extensive writing and editing issues with his daily work as Clerk of Session and Sheriff-Depute of Selkirkshire. Walter Scott was not unaware of Justice and Law and The Heart of Mid-Lothian is the novel in which he introduces to the reader the Scottish Legal System during the eighteenth century. However, there are few more examples that I will explain.